A Case for MOOCs in Indian Higher Education System - Rao, P. N.; Komaraiah, M.; Narasimha Reddy, P. (Journal of Engineering Education Transformations, 2015)
Massive open online courses (MOOC) have started in 2008 but the interest has really exploded since 2012. The proliferation of MOOCs happened because of the maturing of many of the technologies such as the wide availability of low cost broadband, cheaper laptops, tablets, and smart phones, expanded cellular network, cloud storage and computing and social networking. The need for low cost education for masses has been felt and MIT started the open courseware movement, which has been followed by many other big universities. This has naturally progressed into MOOC and a large number of MOOCs have been made available. Because of the openness and online,eager students particularly from developing nations have lapped up MOOCs. India also followed with the IITs and IIM providing themin a smallway.Therewere also efforts to make the MOOCs for credit by some universities. The structure of a MOOC is slightly different from traditional classroom based courses in order to keep the attention of the online student with the course. Therefore, it is necessary to follow the best practices that have proven successful with theMOOCs that are already available. For Indian higher education system, MOOCs actually would provide a very convenient model to impart quality education across a large number of private institutions. It is important to consider a viable model for offering MOOCs as part of regular university curriculumand offer credit at the same time having the flexibility of taking free courses. This paper offers such amodel for Indian universities.